The Chinese School of IR – Success of the Research Program - A. I. Kozinets (Международная аналитика)
The current social organisation of academic science in China has created special conditions for the development of theoretical knowledge in the country. Classical Chinese philosophy, as well as the rich historical experience of interstate relations in East Asia, remains an important component of the successful development of Chinese theories of international relations. At the same time, issues of theory development have for many years occupied a central place in the scientific community of the People’s Republic of China, as has the system of motivation of research personnel and methodological training of researchers. The article examines the main stages in the development of the Chinese school as a non-Western approach to the theory of international relations, playing particular attention to institutional aspects from the perspective of the sociology of science.